Preoperative Strength Training for Elderly Patients Awaiting Total Knee Arthroplasty. (13th February 2014) - van Leeuwen, D. M.; de Ruiter, C. J.; Nolte, P. A.; de Haan, A.
Abstract : Objective . To investigate the feasibility and effects of additional preoperative high intensity strength training for patients awaiting total knee arthroplasty (TKA). Design . Clinical controlled trial. Patients . Twenty-two patients awaiting TKA. Methods . Patients were allocated to a standard training group or a group receiving standard training with additional progressive strength training for 6 weeks. Isometric knee extensor strength, voluntary activation, chair stand, 6-minute walk test (6MWT), and stair climbing were assessed before and after 6 weeks of training and 6 and 12 weeks after TKA. Results . For 3 of the 11 patients in the intensive strength group, training load had to be adjusted because of pain. For both groups combined, improvements in chair stand and 6MWT were observed before surgery, but intensive strength training was not more effective than standard training. Voluntary activation did not change before and after surgery, and postoperative recovery was not different between groups (P > 0.05 ). Knee extensor strength of the affected leg before surgery was significantly associated with 6-minute walk (r = 0.50 ) and the stair climb (r − = 0.58, P < 0.05 ). Conclusion . Intensive strength training was feasible for the majority of patients, but there were no indications that it is more effective than standard training to increase preoperative physical performance. This trial was registered withNTR2278 .